Produção de bioemulsificante por Rhodotorula mucilaginosa UCP 1551 através da bioeconomia circular utilizando substratos agroindustriais. - Lins, Amanda Barbosa (2019)
Brazil ranks third in world food production, where industries are responsible for generating tons of solid waste, leading to serious environmental problems. In this sense, the use of strategies such as circular bioeconomics allows the bioconversion of these residues in products with high added value, such as bioemulsifiers. These compounds have properties such as: detergency, emulsifying activity, lubrication, wettability, solubility and dispersion of compounds hydrophobic in aqueous phases, as well as having low or no toxicity, are biodegradable, resistant to ionic strength, pH and temperature and have specificity. Studies were carried out with Rhodotorula mucilaginosa UCP 1551, investigating the bioemulsifier production potential, using as renewable substrates post-fry soybean oil and corncina. The culture was carried out in 250 ml Erlenmeyer flasks containing 100 mL of salt base, with 10% of inoculum with concentration of 108 cells/mL and the substrates according to the complete factorial design 22, with soybean oil and emulsification index (IE24), incubated at 28 ° C, under agitation of 150 rpm for 96 h. The characteristics of the bioemulsifier were evaluated in relation to emulsification index, emulsion droplet size, viscosity, stability to pH variations, NaCl concentration and temperature, determination of CMC and determination of the capacity as wetting agent. The results showed that the bioemulsifier had an emulsification index of 95.65% for burned engine oil in condition 1 of the planning (2,5% of corncina and 1% of soybean oil after frying), with a stable emulsion against pH, salinity and temperature. Condition 1 had the highest viscosity reduction of the engine oil burned from 170 cP to 115.7 cP after 24 hours of sample rest, killing after 96 hours. The bioemulsifier had a CMC of 2.5%, with a biochemical composition of lipids 78.66%, proteins 14.65% and carbohydrates 6.69%. The new bioemulsifier produced by Rhodotorula mucilaginosa has been shown to be a wetting agent, suggesting future applications in the oil field, in particular in improved oil recovery (MEOR).